2007
DOI: 10.1353/hub.2008.0007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determination of Head-Size-Related Anthropometric Traits in an Ethnically Homogeneous Sample of 373 Indian Pedigrees of West Bengal

Abstract: The substantial involvement of genetic factors in the determination of head-size and head-shape traits has been firmly established. However, there has been a lack of agreement on a number of specific issues concerning the pattern of inheritance of craniofacial features. In this study we examined some of these issues in a large, ethnically homogeneous sample of Indian pedigrees. The data included 1,263 individuals belonging to 373 nuclear families. Eleven raw head-size traits and two synthetic phenotypes, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…Principal shape components associated with the degree of horizontal separation between the eyes, the length, breadth and projection of the nose, and the height and projection of the upper lip all demonstrated high heritability. These findings are largely supported by more traditional anthropometric studies that utilize standard linear distances to quantify facial surface structures [18-20,22-35]. There is also substantial overlap between the results of the present study and those of prior 3D facial surface studies on twin pairs.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Principal shape components associated with the degree of horizontal separation between the eyes, the length, breadth and projection of the nose, and the height and projection of the upper lip all demonstrated high heritability. These findings are largely supported by more traditional anthropometric studies that utilize standard linear distances to quantify facial surface structures [18-20,22-35]. There is also substantial overlap between the results of the present study and those of prior 3D facial surface studies on twin pairs.…”
Section: Discussionsupporting
confidence: 75%
“…Several prior studies report the highest heritability estimates for vertically oriented facial measures [6,9-11,24,54], although there is considerable disagreement on this point [7,14,33-35]. The current findings present a slightly more complex picture.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In recent years, most studies based on this concept assessed 2 common factors: horizontal components (HOCs) and vertical components (VECs). Several investigations found that the genetic effect was estimated differently between 2 factors [8, 10, 14, 18, 19]. In these studies, however, the extraction of common latent variables in facial complex measurements was only limited to HOCs and VECs.…”
Section: Introductionmentioning
confidence: 99%